Analysis of High School Students Mathematical Literacy Skills in the Cambridge Curriculum - Prayuti, Amarta; Ambarwati, Lukita; Sovia, Anny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematical literacy skills are one of the competencies needed in the 21st century. The aim of this study is to describe the mathematical literacy skills of high school students on the Cambridge curriculum angle material. This study was conducted in class X-A MAS Istiqlal Jakarta with 27 research subjects. The research method used a qualitative approach with a descriptive method. The data collection technique used a validated mathematical literacy test consisting of 5 essay questions with three indicators: formulate, employ, and interpret. The results showed that mathematical literacy skills were in the high category of 11%, the medium category was 70%, and the low category was 19%. The majority of students missed the formulate and interpret stages and made process errors at the employ stage